Innovative teaching and learning environment system (iTa’LEem): implementing a state-of-art platform for managing E-learning - Md Ghalib, Mohd. Feham; Mat Ghani, Gairuzazmi (MEIPTA, 2014)
The use of learning management system (LMS) in IIUM was dated back in 2003 through the introduction of LearingCare XT produced by Mitechsoft. Since then the platform had undergone several minor updates to cope with the current needs of the end users. As the time expanded, it faced performance problems and considered outdated. In the IIUM context, there are several LMS platforms implemented by various kulliyyahs or centres of studies, for instance, Kuliyyah of Information & Communication Technology uses Claroline and Centre for Languages (CELPAD) uses Moodle. By the end of 2012, E-learning policy at IIUM had been formulated and endorsed by the university’s senate. Unfortunately, the policy could not be fully implemented due to the inherited limitation in our LMS platform. Thus, there was a need to come up with a recent platform for several reasons; fulfilling the policy requirements, complying to the ministry E-learning Roadmap (DePAN), and achieving the key indicators set for PSPTN E-learning CAP agenda.